2021
DOI: 10.1186/s12864-021-07434-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of 2-oxoglutarate and Fe(II)-dependent dioxygenase family genes in tomato during growth cycle and their roles in metabolism

Abstract: Background 2-Oxoglutarate and Fe(II)-dependent dioxygenases (2ODDs) belong to the 2-oxoglutarate-dependent dioxygenase (2OGD) superfamily and are involved in various vital metabolic pathways of plants at different developmental stages. These proteins have been extensively investigated in multiple model organisms. However, these enzymes have not been systematically analyzed in tomato. In addition, type I flavone synthase (FNSI) belongs to the 2ODD family and contributes to the biosynthesis of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…2-Oxoglutarate/Fe(II)-dependent dioxygenases (2-ODDs), non-heme iron-containing soluble proteins, participate in the synthesis of important plant hormones and diverse secondary metabolites (Farrow and Facchini, 2014;Wei et al, 2021). Flavonoids, the natural products present in plants, possess enormous chemical diversity due to the organization and modifications of the three-ring structure by 2-ODDs, cytochrome P450-dependent oxygenases (CYPs), glycosyltransferase, and O-methyltransferases (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2-Oxoglutarate/Fe(II)-dependent dioxygenases (2-ODDs), non-heme iron-containing soluble proteins, participate in the synthesis of important plant hormones and diverse secondary metabolites (Farrow and Facchini, 2014;Wei et al, 2021). Flavonoids, the natural products present in plants, possess enormous chemical diversity due to the organization and modifications of the three-ring structure by 2-ODDs, cytochrome P450-dependent oxygenases (CYPs), glycosyltransferase, and O-methyltransferases (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we concluded that Pn2-ODD1 contributed to the accumulation of anthocyanins and flavonol in Arabidopsis. 2-ODDs in the flavonoids biosynthesis pathway are involved in the growth and development, as well as stress responses of plants (Wei et al, 2021). Salinity stress can adversely hamper plant germination and growth, transpiration, and photosynthesis, which is one of the major threats to plant productivity (Wang et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FNSIs are soluble 2-oxoglutarate- and Fe 2+ -dependent dioxygenases mainly found in members of the Apiaceae [ 62 ]. Meanwhile, FNSII members belong to the NADPH- and oxygen-dependent cytochrome P450 membrane-bound monooxygenases and are widely distributed in higher plants [ 63 , 64 ]. FNS is the key enzyme in flavone formation.…”
Section: Flavonoid Biosynthesis In Plantsmentioning
confidence: 99%
“…FNS I and FLS belong to the 2-Oxoglutarate-dependent dioxygenase (2ODGs, Kawai et al, 2014 ) superfamily (FNS I into DOXC28 and FLS into DOXC47). Both FNS Ⅰ and FLS can exert catalytic activity in vitro ( Halbwirth et al, 2006 ; Wang Y. et al, 2021 ; Wei et al, 2021 ). The FNS I has a similar structure to the FLS, and the conserved amino acids of FNS I from different sources are also highly conserved in FLS.…”
Section: Introductionmentioning
confidence: 99%